Habilidades de pensamiento creativo en maestros en formación - Villacrez Oliva, María Victoria (Universidad Pedagógica y Tecnológica de Colombia, 2017)
Education requires pedagogical transformations that allow the development of creative thinking skills in learners, from the different areas of knowledge; thus, in the teacher training process it is paramount the importance of thinking, in order to transform the realities of any pedagogical practice. This article showcases the outcomes of a research project, which explores teaching and learning strategies strengthen the creative thinking skills in fifth semesters of the Bachelor Program in Basic Primary Education of the Mariana University. This qualitative study was developed through a process of diagnosis, planning, execution and evaluation of strategies that helped to foster skills such as sensitivity to problems, fluency, flexibility, originality and layout.